2012
DOI: 10.4149/gpb_2012_038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Opuntia ficus indica f. inermis fruit juice hepatoprotective effect upon ethanol toxicity in rats

Abstract: Abstract. The aim of our present study is to investigate the effect of Opuntia ficus indica f. inermis prickly pear juice (PPJ) against ethanol-induced liver injury in rats. Chronic ethanol administration (3 g/kg b.w.) during 90 days to Wistar rats, significantly (p < 0.01) increased the liver lipid and protein oxidation, reduced the glutathione content and the activities of liver antioxidant enzymes such as superoxide dismutase, catalase, glutathione peroxidase and conversely elevated the liver injury biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Chronic alcohol administration (3 g/kg) to Wistar rats for 90 days, significantly increased the liver lipid and protein oxidation (p < 0.01), reduced the GSH content and the activities of liver antioxidant enzymes such as SOD, catalase, GSH and conversely elevated the liver injury biochemical markers such as AST, ALT, ALP, γ-GST, LDH, cholesterol, triglycerides and caused severe histopathologic injuries. Conversely pre-treatment with prickly pear juice (20 and 40 mL/kg, orally) in alcohol-fed rats, decreased liver lipid and protein oxidation and changed histopathologic injury, as well as inhibited the alterations of antioxidant enzymes and the release of biochemical markers [90]. Therefore, Opuntia ficus-indica might be effective in treating hangover and protecting liver from alcohol toxicity due to its anti-inflammatory and strong antioxidant properties.…”
Section: Opuntia Ficus-indicamentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic alcohol administration (3 g/kg) to Wistar rats for 90 days, significantly increased the liver lipid and protein oxidation (p < 0.01), reduced the GSH content and the activities of liver antioxidant enzymes such as SOD, catalase, GSH and conversely elevated the liver injury biochemical markers such as AST, ALT, ALP, γ-GST, LDH, cholesterol, triglycerides and caused severe histopathologic injuries. Conversely pre-treatment with prickly pear juice (20 and 40 mL/kg, orally) in alcohol-fed rats, decreased liver lipid and protein oxidation and changed histopathologic injury, as well as inhibited the alterations of antioxidant enzymes and the release of biochemical markers [90]. Therefore, Opuntia ficus-indica might be effective in treating hangover and protecting liver from alcohol toxicity due to its anti-inflammatory and strong antioxidant properties.…”
Section: Opuntia Ficus-indicamentioning
confidence: 99%
“…Mice Amelioration of liver and brain alcohol injuries through decreasing L-γ-glutamyl transpeptidase and butyryl cholinesterase [76] Humans Decreased signs and symptoms of alcohol hangover [79] Essential oil and citral Mice Hepatoprotective property against AFLD by decreasing levels of D-glucurono-6,3-lactone, glycerol-3-phosphate, and pyruvic acid in serum [80] Opuntia ficus-indica Flavones and phenolics Cladode Humans Reduced hangover symptoms by inflammatory mediator production inhibition [88,89] Rats Suppression of liver damage induced by alcohol through ending free radical chain reactions or enhancing the endogenous antioxidant activities [90] Panax ginseng Ginsenosides Root Humans Relief from hangover symptoms through reduced expiratory and plasma alcohol levels and hangover severity [91] Linoleic acid Mice Alleviation of hangover through reduced alcohol and acetaldehyde levels and enhanced ADH and ALDH activities [92] Mice Suppressed alcohol-induced toxicity on male fertility [93] Ricefish Suppressed alcohol-induced toxicity on embryogenesis [94] Mouse embryos Suppressed alcohol-induced toxicity in the neurocranium through its effects on antioxidant activity [95] Rats Suppressed alcohol-induced toxicity in the gastric system via the restoration of heat-shock proteins [96] Hypericum perforatum Hypericin and hyperforin Leave and flowering tops Rats and mice Reduced voluntary alcohol intake in acute and chronic alcohol treatment through neurochemical mechanisms [101,104,105] Rats Attenuated alcohol withdrawal syndrome by inhibition of the effects on tremors and audiogenic seizures [102] Salvia miltiorrhiza…”
Section: -Gingerol Rhizomementioning
confidence: 99%
“…Also, Orhan and colleagues demonstrated that the extract of Vitis vinifera leaves is able to reduce liver damage caused by carbon tetrachloride [32]. Furthermore, Alimi et al [33] show that the consumption of fruit juice from Cactus opuntiaficusindica f. inermis, which contains antioxidant compounds such as flavonoids polyphenols, betaxanthin and betacyanin reduced levels of AST, ALT and GGT in Wistar rats, suggesting protective role in liver injury induced by ethanol.…”
Section: Discussionmentioning
confidence: 98%
“…[2][3][4] Recent studies have reported that the extract of O. ficus-indica showed antioxidant, antiulcer, neuroprotective, and hepatoprotective activities. [5][6][7][8] To the best of our knowledge, however, the hepatoprotective chemical constituents in this plant against ethanolinduced hepatotoxicity have not been previously reported. Thus, in this study, we attempted to investigate the hepatoprotective constituents of O. ficus-indica using primary rat hepatocytes and HepG2 cells as screening tools.…”
mentioning
confidence: 92%